Restrukturisasi kognitif untuk mengurangi gejala kecemasan pada wanita yang mengalami premenopause - Debby Afradipta (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The subject is 45 years old women who have been divorced since 2013. She has a problem in the form of negative thoughts that lead to symptoms of anxiety and always appear in her life. The assessment methods used were observation, interview, psychological test (WAIS, Graphic, SSCT, and Beck Anxiety Scale). The intervention given is Cognitive Therapy using Cognitive Restructuring techniques. The goal is to reduce the symptoms of anxiety experienced by the subject. After giving the intervention for 6 sessions, she was able to change her views and perceptions with more positive thoughts.